The YellowPress Periodical : #2 : January 2016. - Crombez, Thomas; Dumalin, Caroline; van Gerrewey, Christophe; Gorus, Kim; Heirwegh, Ward; van Pelt, Hilde (Antwerpen : kdG / Sint Lucas Antwerpen, 2016)
Karen Vermeren: Bárðarbunga ; Elke Couchez: A Deep Sense of Place. Unfolding Karen Vermeren's Bárðarbunga ; Octave Vandeweghe: Socially-Engaged and Community-Involved Jewellery Projects ; Kim Gorus: Bad Artists Copy; Good Artists Steal ; Pieter Vermeulen: The Cloud of Unknowing. Or: WTF Happened to Artistic Research? ; Christophe Clarijs: The Subversive Form
YellowPress is the publication platform of St Lucas School of Arts Antwerp. YellowPress lends its services to other researchers and/or platforms. As a research platform it also studies new publication forms for artistic research in the current media landscape. The name YellowPress is an allusion to so-called Yellow Journalism. Yellow journalism is characterized by misleading news, sensationalist pictures, screaming headlines and strong sympathy for the underdog. With an ironic wink to this trivial form of journalism, YellowPress wishes to take the attitude of the professional dilettante - between professional and amateur - as its starting point.
boek